The impact of phishing on privacy attacks in the digital domain (Journal of Imam Al-Kadhim College, 2023)
Abstract:Phishing is one of the most prominent technical means aimed at get the personal data of Internet users, such as credit card details, passwords for their accounts, and their real names, and using that data for illegal purposes. network by asking him to enter a specific link or put a number to call him to enable the phisher to seize his personal data, disable his phone or computer, or spy on him.
Keywords: phishing, privacy, digital domain